2009
DOI: 10.1126/science.1180962
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid-β Dynamics Are Regulated by Orexin and the Sleep-Wake Cycle

Abstract: Amyloid-β (Aβ) accumulation in the brain extracellular space is a hallmark of Alzheimer's disease (AD). The factors regulating this process are only partly understood. Aβ aggregation is a concentration-dependent process that is likely to be dependent on changes in brain interstitial fluid (ISF) levels of Aβ. Using in vivo microdialysis, we found that ISF Aβ levels correlated with wakefulness. ISF Aβ levels also significantly increased during acute sleep deprivation and during orexin infusion, whereas they decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

40
1,152
4
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 1,321 publications
(1,257 citation statements)
references
References 14 publications
40
1,152
4
4
Order By: Relevance
“…In both in vitro and in vivo experiments with activity-induced secretion, the concentration of extracellular A β remains in the picomolar range. This concentration range of A β was also measured in the ISF of mice subjected to a circadian rhythm, with more elevated levels when awake (Kang et al , 2009 ). Moreover, other authors reported that A β levels in the picomolar range enhanced synaptic plasticity and memory (Puzzo et al , 2008 ;Garcia -Osta and Alberini, 2009 ).…”
Section: App Metabolism and A β Formationsupporting
confidence: 52%
“…In both in vitro and in vivo experiments with activity-induced secretion, the concentration of extracellular A β remains in the picomolar range. This concentration range of A β was also measured in the ISF of mice subjected to a circadian rhythm, with more elevated levels when awake (Kang et al , 2009 ). Moreover, other authors reported that A β levels in the picomolar range enhanced synaptic plasticity and memory (Puzzo et al , 2008 ;Garcia -Osta and Alberini, 2009 ).…”
Section: App Metabolism and A β Formationsupporting
confidence: 52%
“…Together, these findings indicate that high‐quality sleep can mitigate Alzheimer's disease pathology. A connection between Aβ and NREM sleep has been found in rodent models (Kang et al, 2009; Roh et al, 2012). Investigating the underlying mechanisms of sleep, a recent study discovered a sleep‐dependent role for the lymphatic system in Aβ clearance (Xie et al, 2013).…”
Section: Lifestyle Associations and Interventions For Aging And Admentioning
confidence: 96%
“…This results in enhanced clearance of Aβ and other compounds. Conversely, the waking brain state can contribute to accumulation of Aβ (Kang et al, 2009), specifically through a higher neurometabolic rate relative to NREM sleep (Buchsbaum et al, 1989). Neurons consume greater levels of oxygen and ATP during wakefulness (Braun et al, 1997; Dworak, McCarley, Kim, Kalinchuk, & Basheer, 2010), while NREM sleep is associated with reduced oxygen consumption and active replenishment of ATP levels (Braun et al, 1997; Dworak et al, 2010).…”
Section: Lifestyle Associations and Interventions For Aging And Admentioning
confidence: 99%
“…237 The 42-residue amyloid-b (Ab) protein fragment is produced through cleavages, by proteases of the secretase family, from the transmembrane amyloid precursor protein (APP). Upon its formation at the cell's plasma membrane, Ab becomes largely extracellular but can also be found in the cytoplasm.…”
Section: The Amyloid-b (Ab) Protein Fragmentmentioning
confidence: 99%